309 MOTILITY DISTURBANCES IN EOSINOPHILIC ESOPHAGITIS: A CASE SERIES. Issue 1 (1st January 2007) - Reddymasu, S. C.; Westoff, B.; Olayee, M.; McCallum, R. W.
Abstract : Background: Eosinophilic esophagitits (EE) is a distinct clinicopathologic condition first described in 1978 when it was initially recognized as an important cause of dysphagia in children. Of late, it is being reported more often in the adult population also, especially males. Key to diagnosis is finding mucosal eosinophils in the esophagus, specifically the proximal esophagus. Although dysphagia is the major complaint in these patients, there is little information as to whether an esophageal motility disturbance could accompany this entity. Aims of the Study: To review the results of esophageal motility studies in patients diagnosed with EE at the Kansas University Medical Center. Methods: Patients whose proximal esophageal biopsy was consistent with EE were included in the study. Four patients were identified who also underwent esophageal manometry for complaints of dysphagia and subsequently had endoscopy with esophageal biopsies performed. Results: All the patients had the typical "ringed" esophagus and a corrugated appearance on endoscopy. Two of the four patients had accompanying symptoms of gastroesophageal reflux disease (GERD). Pharyngeal function, peristaltic motility of the esophageal body, contraction amplitudes, and the lower esophageal sphincter were normal in all patients. One patient had a LES pressure of 15 mm Hg, which was low normal (normal 15-35 mm Hg). This patient was being treated for GERD. Discussion: None of the patients had significant abnormalities by esophageal manometry to explain their dysphagia. Although dysphagia is a common complaint in EE, the pathogenic mechanism for this complaint is not clearly known. It is speculated that eosinophils proliferate the muscular layer in patients with EE and release histamine and other chemokines in response to exposure to allergens, which, in turn, induces dysphagia. Isolated case reports in the past have suggested that high-amplitude esophageal body contractions and impaired esophageal peristalsis could be found on esophageal manometry in patients with EE. These changes could not be reproduced in our study, although the procedure was performed when patients were asymptomatic, and perhaps this could change during episodes of dysphagia. Conclusions: EE is not associated with any specific abnormalities of esophageal manometry. Dysphagia not explained by esophageal manometry or by findings from endoscopic and imaging studies of the esophagus should raise suspicion for EE.